AWS Certified DevOps Engineer - Professional Certification and Beyond - Book, Adam (Packt Publishing, 2021)
Explore the ins and outs of becoming an AWS certified DevOps professional engineer with the help of easy-to-follow practical examples and detailed explanations Key Features Discover how to implement and manage continuous delivery systems and methodologies on AWS Explore real-world scenarios and hands-on examples that will prepare you to take the DOP-C01 exam with confidence Learn from enterprise DevOps scenarios to prepare fully for the AWS certification exam Book Description The AWS Certified DevOps Engineer certification is one of the highest AWS credentials, vastly recognized in cloud computing or software development industries. This book is an extensive guide to helping you strengthen your DevOps skills as you work with your AWS workloads on a day-to-day basis. You'll begin by learning how to create and deploy a workload using the AWS code suite of tools, and then move on to adding monitoring and fault tolerance to your workload. You'll explore enterprise scenarios that'll help you to understand various AWS tools and services. This book is packed with detailed explanations of essential concepts to help you get to grips with the domains needed to pass the DevOps professional exam. As you advance, you'll delve into AWS with the help of hands-on examples and practice questions to gain a holistic understanding of the services covered in the AWS DevOps professional exam. Throughout the book, you'll find real-world scenarios that you can easily incorporate in your daily activities when working with AWS, making you a valuable asset for any organization. By the end of this AWS certification book, you'll have gained the knowledge needed to pass the AWS Certified DevOps Engineer exam, and be able to implement different techniques for delivering each service in real-world scenarios. What you will learn Automate your pipelines, build phases, and deployments with AWS-native tooling Discover how to implement logging and monitoring using AWS-native tooling Gain a solid understanding of the services included in the AWS DevOps Professional exam Reinforce security practices on the AWS platform from an exam point of view Find out how to automatically enforce standards and policies in AWS environments Explore AWS best practices and anti-patterns Enhance your core AWS skills with the help of exercises and practice tests Who this book is for This book is for AWS developers and SysOps administrators looking to advance their careers by achieving the highly sough...